Perceptions of distributive justice in Latin America during a period of falling inequality - Germán Reyes; Leonardo Gasparini (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2017)
In this paper we explore perceptions of distributive justice in Latin America during the 2000s and its relationship with income inequality. In line with the fall in income inequality in the region, we document a widespread, although modest, decrease in the share of the population that believes income distribution is unfair. The fall in the perception of unfairness holds across very heterogeneous groups of the population. Moreover, perceptions evolved in the same direction as income inequality for 17 out of the 18 countries for which microdata is available. Our analysis reveals unfairness perceptions are more correlated with relative measures of income inequality than absolute ones and that individual characteristics are correlated with distributive perceptions. On average, individuals that are older, more educated, unemployed, and left-wing tend to perceive income distribution as more unfair. We show that the decrease in unfairness perceptions during the last decade was due to changes in inequality, rather than to composition effects. Finally, we show that individuals that perceive income distribution as very unfair are more prone to mobilize and protest.
Keywords: D31; D63; D83; 330; Inequality; Fairness; Distributive Justice; Perceptions; Latin America